Quantitative analysis of relationships between irradiation parameters and the reproducibility of cyclotron-produced 99mTc yields. (24th April 2015) - Tanguay, J; Hou, X; Buckley, K; Schaffer, P; Bénard, F; Ruth, T J; Celler, A
Abstract: Cyclotron production of 99m Tc through the 100 Mo(p, 2n) 99m Tc reaction channel is actively being investigated as an alternative to reactor-based 99 Mo generation by nuclear fission of 235 U. An exciting aspect of this approach is that it can be implemented using currently-existing cyclotron infrastructure to supplement, or potentially replace, conventional 99m Tc production methods that are based on aging and increasingly unreliable nuclear reactors. Successful implementation will require consistent production of large quantities of high-radionuclidic-purity 99m Tc. However, variations in proton beam currents and the thickness and isotopic composition of enriched 100 Mo targets, in addition to other irradiation parameters, may degrade reproducibility of both radionuclidic purity and absolute 99m Tc yields. The purpose of this article is to present a method for quantifying relationships between random variations in production parameters, including 100 Mo target thicknesses and proton beam currents, and reproducibility of absolute 99m Tc yields (defined as the end of bombardment (EOB) 99m Tc activity). Using the concepts of linear error propagation and the theory of stochastic point processes, we derive a mathematical expression that quantifies the influence of variations in various irradiation parameters on yield reproducibility, quantified in terms of the coefficient of variation of the EOB 99m Tc activity. The utility of the developed formalism is demonstrated with an example. We show that achieving less than 20% variability in 99m Tc yields will require highly-reproducible target thicknesses and proton currents. These results are related to the service rate which is defined as the percentage of 99m Tc production runs that meet the minimum daily requirement of one (or many) nuclear medicine departments. For example, we show that achieving service rates of 84.0%, 97.5% and 99.9% with 20% variations in target thicknesses requires producing on average 1.2, 1.5 and 1.9 times the minimum daily activity requirement. The irradiation parameters that would be required to achieve these service rates are described. We believe the developed formalism will aid in the development of quality-control criteria required to ensure consistent supply of large quantities of high-radionuclidic-purity cyclotron-produced 99m Tc.